Analisis Faktor Faktor yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan PT Blue Bird TBK : Studi Kasus 2020-2022 - Gina Fauziah; Rina Maria Hendriyani (Journal of Management and Creative Business, 2026)
This study aims to determine and analyze the factors affecting the timeliness of financial reporting at PT Blue Bird. The object of this study is PT Blue Bird, using the company's financial statements for the 2020–2022 period as the primary source of data. The independent variables examined are profitability and leverage, while the dependent variable is the timeliness of financial reporting. This research employs a quantitative approach using secondary data collected from the company's published financial reports. Multiple linear regression analysis is applied to examine the relationship between the independent and dependent variables, with the t-test and F-test used to evaluate the research hypotheses. The findings indicate that profitability has a positive and statistically significant partial effect on the timeliness of financial reporting. Likewise, leverage also demonstrates a positive and significant partial effect on reporting timeliness. Simultaneously, profitability and leverage significantly influence the timeliness of financial reporting. These findings suggest that stronger financial performance and appropriate debt management contribute to more timely financial reporting, thereby improving transparency, supporting informed decision-making by stakeholders, and enhancing the credibility and accountability of corporate financial information.